Diversity Of Weed Flora from Different Land Preparations from Oil Palm Plantation - Ailen, Shia Sikin (Universiti Malaysia Sarawak, (UNIMAS), 2012)
Weeds have brought many problems in oil palm plantation. Applied method of land preparation for oil palm plantation involved burning and zero burning. The study in this project is mainly i) to determine the diversity of weed flora, ii) to estimate total biomass and carbon stock content of weed flora in different land preparation; burned, natural burned and unburned peatland for oil palm plantation FELCRA oil palm plantation in Melur Gemilang, Gedong, Kota Samarahan. Species diversity is determined by using Shannon-Weiner Diversity Index (H’), Species Eveness (J’), Summed Dominance Ratio (SDR) and the estimation of carbon stocks is calculated by using method by Pearson. Fifty quadrats of 1m x 1m were established in each study area within March and April 2012. There were total of 48 species found belongs to 39 genera and 27 families. The species diversity in natural burned land, H’= 1.57 is the highest compare to unburned land (H’=0.65) and burned land (H’=0.93). Stenochlaena palustris is the most even species, J’= 0.039 in unburned land. The dominant species determined in these three sites are Nephrolepis biserrata, SDR=60.58% in burned land, SDR=46.28% in natural burned land SDR=62.44% in unburned land. Carbon stock estimation in each sites are 212.16 kg C ha- 1 in burned land, 429.95 kg C ha-1 in natural burned land and the highest in 456.541 kg C ha-1 in unburned land. Total carbon stock produced in peatland studied was 1098.66 kg C ha-1 (1.01 tonne C ha-1 ).